Tendencies to Formalizing Aesthetics - Gaižutis, Algirdas (Problemos, 1982)
Some modem tendencies to formalizing aesthetics are observed in the article, their links with the classical Fechnerian-Herbartian tradition, the role of applying exact methods in aesthetics to make it autonomous as a multi-plane science with an experimental basis of its own, with great prospects, are observed in the article. It is emphasized, at the same time, that an artificial opposition of “traditional” methods to “modern” ones in aesthetics is found to be of little constructiveness since it is impossible to understand the nature of aesthetics and art values when tearing them off from history.